United We Stand: Lived Experiences of Nurses in Interprofessional Collaboration (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
IntroductionA thriving team operates cohesively, exemplifying effective collaboration. In nursing, collaboration plays an integral role, profoundly influencing patient outcomes through the synergy of teamwork. This study explored the lived experiences of nurses engaged in interpersonal collaboration, a multidisciplinary approach in which professionals from diverse fields converge with a shared perspective on delivering patient care. The pivotal question guiding this investigation was, "What are the experiences of staff nurses regarding inter-professional collaboration?"  MethodThis study embraced the qualitative research paradigm to comprehensively present participants' lived experiences, specifically employing Husserlian Phenomenology. This method enabled the unveiling and elucidation of the structures and forms inherent in conscious experiences. At its core, Husserlian Phenomenology starts by encapsulating a person's encounter with an experience. According to Husserl's philosophy, phenomenology delves into consciousness without confining the objective and collective meanings of experiences solely to subjective occurrences (Walters, 2017). Thus, employing descriptive phenomenology, this research delved deeply into the narratives of nurses deeply involved in inter-professional collaboration. By scrutinizing consciousness without reducing the objective and shareable meanings of experiences to mere subjectivity, this approach was aptly suited for investigating nurses' lived encounters within the inter-professional collaboration. The participants were thoughtfully selected through unstructured interviews, a methodology employed to collect rich and insightful data. Before commencement, the Union Christian College Ethics Review Board meticulously reviewed and sanctioned the research to ensure its credibility. The data collection spanned from May to July 2022, involving 10 participants. The participants' profound narratives were skillfully extracted through unstructured interviews. The Giorgi steps were employed in the subsequent data analysis phase to illuminate the nuances of nurses' collaborative experiences. FindingsThree dominant themes emerged from the comprehensive exploration: (1) "Stormy Days," denoting challenges and struggles, (2) "An Umbrella," encapsulating defense mechanisms and coping strategies; and (3) "A Lightbulb," signifying insightful learnings. These themes organically arose from the participants' accounts, echoing their journeys of inter-professional collaboration within the healthcare team. These narratives also portrayed how the participants navigated challenges, resolved conflicts, and engaged with fellow team members. DiscussionsDrawing from the insights gleaned from this study, several recommendations surfaced: Administrators might contemplate fostering constant communication among all health team members through diverse strategies like regular meetings, professional development initiatives, and team-building activities. For thorny issues necessitating resolution and proactive engagement, specialized conflict resolution and engagement strategies could be prudent. Financial concerns identified in the study could potentially be addressed through salary adjustments, enhancing the financial well-being of healthcare professionals. To cement and enhance inter-professional collaboration across the healthcare spectrum, the proposition of a Comprehensive Enhancement Program garnered attention. In sum, this research underscored the significance of inter-professional collaboration in nursing, attesting to the participants’ experiential insights. Through challenges and triumphs alike, these nurses’ stories illuminated pathways for smoother collaboration and problem-solving within multidisciplinary healthcare settings. This study’s findings offer concrete recommendations for healthcare administrators to amplify collaboration, ameliorate conflicts, and augment the overall effectiveness of inter-professional teamwork.
Keywords: Lived experiences; interprofessional collaboration; challenges